Innate lymphoid cells as novel regulators of obesity and its‐associated metabolic dysfunction. (7th March 2016) - Yang, D.; Yang, W.; Tian, Z.; van Velkinburgh, J. C.; Song, J.; Wu, Y.; Ni, B.
Summary: The increased prevalence of obesity worldwide has been accompanied by increases in risk and rates of obesity‐associated metabolic dysfunctions, such as insulin resistance. The chronic, low‐grade inflammatory condition of obesity highlights the pathophysiological link between the immune system and the metabolic system, which has yet to be fully understood. Recent studies of obesity have started to uncover potential regulatory roles for the innate lymphoid cells (ILCs), which under normal conditions serve to regulate development of lymphoid tissue and function of the mucosal immune system. The ILCs are a newly identified immune cell population with complicated composition and subsequently diverse and dynamic functions. Studies to determine the distribution profile of the various ILCs in adipose tissue provide intriguing clues as to their regulatory capacity in obesity and its associated metabolic dysfunctions. Here, we review the recent findings supporting a role for ILCs as regulators of obesity or its associated insulin resistance, and discuss the potential underlying molecular mechanism as well as its promise as a therapeutic target for clinical applications. © 2016 World Obesity